2023
DOI: 10.1007/s40291-023-00678-7
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Inflammatory Bowel Disease

Jasmina El Hadad,
Philipp Schreiner,
Stephan R. Vavricka
et al.

Abstract: The genetic background of inflammatory bowel disease, both Crohn’s disease and ulcerative colitis, has been known for more than 2 decades. In the last 20 years, genome-wide association studies have dramatically increased our knowledge on the genetics of inflammatory bowel disease with more than 200 risk genes having been identified. Paralleling this increasing knowledge, the armamentarium of inflammatory bowel disease medications has been growing constantly. With more available therapeutic options, treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Chronic and relapsing mucosal tissue damage followed by wound healing is a key feature of Inflammatory bowel disease (IBD), which presents as Crohn's colitis (CC) and ulcerative colitis (UC) [36]. Severe intestinal inflammation leads to epithelial loss and degradation of the extracellular matrix, which is clinically evident as erosions or ulcers.…”
Section: Colonmentioning
confidence: 99%
“…Chronic and relapsing mucosal tissue damage followed by wound healing is a key feature of Inflammatory bowel disease (IBD), which presents as Crohn's colitis (CC) and ulcerative colitis (UC) [36]. Severe intestinal inflammation leads to epithelial loss and degradation of the extracellular matrix, which is clinically evident as erosions or ulcers.…”
Section: Colonmentioning
confidence: 99%
“…51,54,55 The HLA genes are responsible for producing proteins that present antigens to T cells, triggering a T-cellmediated immune response, 56 which plays a key role in autoimmune conditions due to mechanisms such as molecular mimicry. [56][57][58] It is suggested that molecular mimicry is one of the principal mechanisms that foreign antigens lead to autoimmunity. 57,59 This occurs when cross-reactive epitopes are displayed via the MHC, leading to an immune response through T-cell activation.…”
Section: Baseline Demographic and Clinical Characteristicsmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 This immune response is inherently linked to the genetic makeup of an individual; however, studies show varying proportions of heritability. 7 , 8 , 9 , 10 Studies have also strongly linked IBD development with factors such as the gut microbiome, 11 the use of antibiotics, 12 and diet. 12 Unraveling such biological complexity necessitates targeted-omics studies, with metabolomics recently helping to identify distinct disease-related patterns 13 , 14 , 15 , 16 , 17 and key differences between individuals with IBD and those without.…”
Section: Introductionmentioning
confidence: 99%